Effect of Curcumin on Beta-Amyloid Plasma Level in Alzheimer Disease: A Systematic Review and Meta-analysis - Shima Mehrabadi (Shahid Beheshti University of Medical Sciences, 2021)
Alzheimer’s disease is known as a most common dementia disorder in the world. The famous hypothesis about the cause of this disease is beta-amyloid (Aβ ) accumulation in the brain. There is a widespread neuroinflammation in the patient’s brain, leading to neuronal apoptosis and brain atrophy. Curcumin is a well-known anti-inflammation and anti-oxidant ingredient. It can easily cross the blood-brain barrier. There are controversial results about the effects of curcumin on Aβ clearance and metabolism in Alzheimer’s disease and the elderly. The aim of this meta-analysis and systematic review was to review the effect of curcumin on Aβ clearance in clinical studies. We performed a systematic review and meta-analysis on the three randomized clinical trials (RCTs) and one pilot study that assessed the effect of curcumin on Aβ plasma level in Alzheimer’s disease. For this purpose, we searched PubMed and Scopus databases up to December 2020. Our result showed there was no significant change in serum Aβ level (weighted mean difference [WMD]: 5.3, 95% CI: 0.78-9.97) following curcumin consumption in patients with Alzheimer’s disease. Further clinical trials should be done to evaluate the effects of curcumin in Aβ level in Alzheimer’s disease.